2022-RA-921-ESGO Systematic nurse-led consultations based on electronic patient-reported outcomes among women with gynaecological cancer during chemotherapy-The CONNECT study. (20th October 2022) - Christiansen, Mille Guldager; Pappot, Helle; Jarden, Mary; Mirza, Mansoor Raza; Piil, Karin
Abstract : Introduction/Background: During chemotherapy, women with ovarian and endometrial cancer experience a significant physical and psychological burden due to the disease and treatment. Patient-reported outcomes (PRO) can help enhance patient-clinician communication, symptom management, patient satisfaction, and quality of life (HRQoL), and electronic PRO (ePRO) can provide appropriate and continuous symptom monitoring. The objective of this study is to develop and investigate the feasibility and effect of systematic nurse-led consultations based on ePRO integrated into a multidisciplinary treatment regimen for patients with ovarian- and endometrial cancer on HRQoL. Methodology: A quasi-experimental four-phase, sequential cohort research design with comparisons between non-equivalent groups. This study will examine: 1) the frequency and severity of clinician-reported symptoms and adverse events, HRQoL (EORTC QLQ-C30+ OV-28/EN-24), levels of anxiety and depressive symptoms (HADS), and self-efficacy (SES6G) among women with ovarian- or endometrial cancer receiving standard care (n=41), 2) developmental phase, 3) test the feasibility of systematic nurse-led consultations based on ePRO (n=20), 4) estimate the effect of the ePRO based model on frequency and severity of nurse-reported symptoms and adverse events, HRQoL, HADS, and SES6G compared to standard care (n=41). The difference in global HRQoL (EORTC QLQ-C30) after 9 months will be the primary outcome. Further, we will conduct qualitative individual and focus-group interviews to explore experiences and satisfaction among patients, nurses, and physicians. Results: We will involve a patient advisory board throughout the research phases to provide research feedback, comment on written materials, and contribute to the research's progress. In addition, the algorithms on the ePRO platform separate the patient's response to symptom severity into three levels. Conclusion: We hypothesize that proactive use of ePRO in nurse-led consultations may contribute to increased quality of life, symptom- and self-management, and CONNECTion between patients and healthcare professionals.